The construction of political journalism: A microanalytic approach. (March 2019) - Bull, Peter
Abstract: In this article, the construction of political journalism is analysed from the perspective of microanalysis. Four published studies are reviewed, based on two specific journalistic contexts: broadcast political interviews (Bull, 2003; Bull and Elliott, 1998; Elliott and Bull, 1996), and news bulletins (Bull et al., 2014). In addition, a further illustrative example is presented, based on a previously unpublished analysis of a television interview with the current British Prime Minister (PM), Theresa May. In the study of the television news, editing techniques of de-contextualization and re-contextualization are identified and discussed in the context of interpretive journalism. All the analyses of interviews are focused specifically on how equivocal responses by politicians occur in response to interviewer questions, which create communicative conflicts through threats to face. From this perspective, equivocal and evasive discourse in political interviews needs to be understood in the broader context of questioning techniques as utilised by political journalists, not simply ascribed to the intrinsic slipperiness of individual politicians. Hence, these studies are of particular relevance to one of the main themes of this special issue, to "journalistic ways of contesting and reclaiming representations of facts".